Diagnostic Criteria for Adult-Onset Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis (PFAPA) Syndrome - Cantarini, Luca; Vitale, Antonio; Sicignano, Ludovico Luca; Emmi, Giacomo; Verrecchia, Elena; Patisso, Isabella; Cerrito, Lucia; Fabiani, Claudia; Cevenini, Gabriele; Frediani, Bruno; Galeazzi, Mauro; Rigante, Donato; et al. (Frontiers in Immunology, 2017)
Objective: To identify a set of variables that could discriminate patients with adult-onset PFAPA syndrome from subjects with fever of unknown origin (FUO). Methods: We enrolled 74 adults diagnosed with PFAPA syndrome according to the currently used pediatric diagnostic criteria and 62 additional patients with FUO. After having collected clinical and laboratory data from both groups, monovariate and multivariate analysis was performed in order to identify the variables associated with PFAPA diagnosis. Odds ratio (OR) values, their statistical significance and corresponding 95% confidence interval (CI) were evaluated for each diagnostic factor both at the monovariate and multivariate analysis. Diagnostic accuracy was evaluated by the area under receiver operating characteristic curve, while the leave-one-out cross-validation procedure was used to ensure that the model maintains the same diagnostic power when applied to new data Results: According to the multivariate analysis, the clinical variables that discriminated PFAPA patients were: fever episodes associated with cervical lymphadenitis (OR=92; p<0.0001), fever attacks associated with erythematous pharyngitis (OR=231; p<0.0001), increased inflammatory markers during fever attacks (OR=588; p=0.001) and the lack of clinical and laboratory signs of inflammation between flares (OR=1202; p<0.0001). These variables were considered for a diagnostic model which accounted for their OR values. The diagnostic accuracy of the proposed set of criteria corresponded to an area under receiver operating characteristic curve of 0.978 (95% CI 0.958-0.998), with a model sensitivity and specificity equal to 93.4% (95% CI 87.5%-96.5%) and 91.7% (95% CI 82.8%-96.7%), respectively. Conclusions: we have provided herein a set of clinical diagnostic criteria for adult-onset PFAPA syndrome. Our criteria represent an easy-to-use diagnostic tool aimed at identifying PFAPA patients among subjects with FUO with a high predictive potential, as shown by its very high sensitivity and specificity.